Reutilización de residuos agroindustriales, cáscara de espárrago (Asparagus officinalis l.) en la fabricación de fibras aglomeradas por buenas prácticas ambientales - Alcantara Revilla, Aníbal Rivelino (2019)
ABSTRACT In the present work we proceeded to reuse the agroindustrial waste, asparagus husk (Asparagus officinalis L.) and the evaluation of the physical and mechanical properties of fiberboard boards made with secondary recycled fibers such as newspaper, cardboard, paper file etc.., etc. For the elaboration of the boards the method of lamination was used. The raw material (newsprint) was characterized, finding a significant amount of residual lignin (25.69%) that allowed the consolidation of the boards. According to the evaluation of the physical properties it was observed that for the tests of increase in mass and in volume by absorption of water, the boards obtained values that disqualifies them, however, it should be noted that rosin was not used to improve this property. With respect to the density values were obtained that qualify the boards as "hardboard" and the whiteness was affected as the consolidation temperature was increased. Within the mechanical tests hardness tests were carried out, reaching values comparable to hard plastic (virgin polypropylene), and flexion tests were performed for both the MOR and MOE, obtaining results with lower yields than those mentioned by other authors, however, the values of the present work are within the range that the authors mention.